2007
DOI: 10.1038/sj.npp.1301500
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Safety and Efficacy of Dapoxetine in the Treatment of Premature Ejaculation: A Double-Blind, Placebo-Controlled, Fixed-Dose, Randomized Study

Abstract: The aim of the study was to evaluate the efficacy and safety of a selective serotonin reuptake inhibitor (SSRI) drug dapoxetine in delaying ejaculation in patients with premature ejaculation (PE). A total of 212 potent men with PE were randomly assigned to receive 30 mg orally dapoxetine (group 1, N ¼ 106) twice daily or similar regimen of placebo (group 2, N ¼ 106) during a 12-week period for each agent. Pretreatment evaluation included history and physical examination, geometric mean intravaginal ejaculatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 32 publications
2
58
0
2
Order By: Relevance
“…Additional adverse event data not included in reviews was available from eleven RCTs. (Atmaca et al 2002;Biri et al 1998;Manasia et al 2003;McMahon 1998;Mendels et al 1995;Murat Basar et al 1999;Safarinejad & Hosseini 2006;Safarinejad 2006;Waldinger et al 1994;Waldinger et al 1997;Waldinger et al 2003;Yilmaz et al 1999) However, these data tended to be greater detail regarding types of adverse events and numbers of participants (Supplementary table ), and did not conflict with any conclusions regarding between-group differences in adverse events (e.g., reported p-values) presented in existing reviews. Furthermore, due to diversity of the types of adverse events these data did not facilitate any data pooling across RCTs for adverse events in the HTA short report (Cooper et al 2013).…”
Section: Completeness Of Outcome Data From Existing Reviewsmentioning
confidence: 51%
See 1 more Smart Citation
“…Additional adverse event data not included in reviews was available from eleven RCTs. (Atmaca et al 2002;Biri et al 1998;Manasia et al 2003;McMahon 1998;Mendels et al 1995;Murat Basar et al 1999;Safarinejad & Hosseini 2006;Safarinejad 2006;Waldinger et al 1994;Waldinger et al 1997;Waldinger et al 2003;Yilmaz et al 1999) However, these data tended to be greater detail regarding types of adverse events and numbers of participants (Supplementary table ), and did not conflict with any conclusions regarding between-group differences in adverse events (e.g., reported p-values) presented in existing reviews. Furthermore, due to diversity of the types of adverse events these data did not facilitate any data pooling across RCTs for adverse events in the HTA short report (Cooper et al 2013).…”
Section: Completeness Of Outcome Data From Existing Reviewsmentioning
confidence: 51%
“…A total of 41 RCTs that evaluated an SSRI against a comparator (placebo, no therapy, another SSRI, or another agent) were identified and were included in both the rapid review for the HTA short report and the full systematic review. Twenty-five of these RCTs (Atmaca et al 2002;Atmaca et al 2003;Biri et al 1998;Buvat et al 2009;Kara et al 1996;Kaufman et al 2009;Manasia et al 2003;Mattos et al 2008;McMahon 1998;McMahon et al 2010;Mendels et al 1995;Murat Basar et al 1999;Panshou and Xie 2004;Pryor et al 2006;Safarinejad and Hosseini 2006;Safarinejad 2008;Safarinejad 2006;Waldinger et al 1994;Waldinger et al 1997;Waldinger et al 1998;Waldinger et al 2001a;Waldinger et al 2001b;Waldinger et al 2003;Yilmaz et al 1999;Zhou 2007) had been previously included by eleven systematic reviews ( Data from these 25 RCTs were extracted from the systematic reviews they were reported in for the rapid review, and directly from the RCT publication obtained in full for the full systematic review.…”
Section: Search Resultsmentioning
confidence: 99%
“…Sir, A recent article by MR Safarinejad published in Neuropsychopharmacology contained results from a randomized, double-blind, placebo-controlled trial of dapoxetine for the treatment of premature ejaculation (PE) (Safarinejad, 2008). In this publication, and in a related article published previously by the same author, (Safarinejad, 2006) several major differences are noted compared to the phase III studies used to investigate the safety and efficacy of dapoxetine (Pryor et al, 2006).…”
mentioning
confidence: 93%
“…In this publication, and in a related article published previously by the same author, (Safarinejad, 2006) several major differences are noted compared to the phase III studies used to investigate the safety and efficacy of dapoxetine (Pryor et al, 2006).…”
mentioning
confidence: 99%
“…Mild side effects were reported in eight patients (13.3%), consisting of mild dyspepsia and somnolence. In another study, Safarinejad and Hosseini performed a double-blind, placebo-controlled, fixed-dose, randomized study to evaluate the efficacy and safety of tramadol (Safarinejad & Hosseini, 2006). They randomly assigned 64 potent men with PE to receive 50 mg tramadol or placebo and showed an increase in IELT from 19 seconds to over 4 minutes in the tramadol arm.…”
Section: Tramadolmentioning
confidence: 99%